Interaksi Simbolik untuk Akuntansi Sektor Publik - Razak, A. (Eksos, 2023)
This research is important, especially to explore further the behavioral aspects behind the budget. Researchers want to get a more real and definite picture of who is behind the power in the process of preparing the Regional Government budget. how their life and behavior; how they think and make decisions; as well as other people around them. All of these aspects may very well influence the behavior of the executive and legislature in the practice of decision-making in the process of drafting the Regional Government budget that has been running so far. Based on the problems above, the goal to be achieved is "understanding the behavior of the executive and legislature in the process of preparing the Government budget" and the importance of understanding symbols when someone uses Symbolic Interaction theory. Symbols are social objects in an interaction. It is used as representation and communication which is determined by the people who use it. These people give meaning, create and change the object in the interaction. These social symbols can be in the form of physical objects (objects that are visible to the eye), words (which are used to represent physical objects, feelings, ideas, etc.), and actions (whatever people do). often gives meaning to communicate with others).